Determination of the antioxidant potential of processing products of osmotically dehydrated chokeberry fruits and beer enriched with them - Samilyk, Maryna; Illiashenko, Yana; Rudichenko, Yevhen; Yevtushenko, Yevhen; Huba, Svitlana; Tkachuk, Svetlana; Ryzhkova, Taisia; Heida, Iryna; Lysenko, Hanna; Severin, Raisa (Eastern-European Journal of Enterprise Technologies, 2024)
The demand for functional and health products, as well as the depletion of traditional raw materials, encourages the use of new types of resources. Aronia melanocarpa is a non-traditional plant raw material that has significant potential but is almost never used in the food industry. The aim of this study is to determine the antioxidant potential of processed products of osmotically dehydrated chokeberry fruits and beer enriched with them. The object of the study is the processing products of osmotically dehydrated chokeberry fruits and beer enriched with them. Chokeberry fruits were dehydrated by osmotic dehydration and drying, ground into powders, and their antioxidant properties were determined. Osmotic solutions and fresh fruits were analyzed for flavonoids, anthocyanins and antioxidant activity. Three experimental samples of beer were produced using traditional technology (K) and with the addition of 6 % (D1) and 10 % (D2) osmotic solutions separated from partially dehydrated fruits. An organoleptic analysis of beer was carried out and its antioxidant activity was determined. The results showed that when using osmotic dehydration, the loss of flavonoids was significantly less (29.74 mg K/100 g) than when using the traditional drying method (39.13 mg K/100 g). When applying the proposed regime of fruit dehydration, about 70 % of anthocyanins are retained. While the traditional method preserves only 59 % of these pigments. The sugar solution on the surface of the fruit prevents significant loss of antioxidant compounds. This explains the higher antioxidant activity (9.86 mmol Trolox/100 g) in samples dehydrated using osmotic dehydration. Adding a chokeberry osmotic solution to beer in an amount of 6–10 % leads to an increase in its antioxidant activity by 9–16 mmol Trolox/100 g